Shenqi compound enhances pancreatic β-cell secretion by promoting the maturation and transport of insulin secretory vesicles through the NOD1/RIP2 signaling pathway - Yao, Nairong; Xing, Yiqian; Tang, Ruobing; Xie, Chunguang; Yang, Qiyue; Liu, Ya; Zhang, Xiyu (Frontiers in Nutrition, 2026)
BackgroundShenqi compound (SQC) is an effective prescription in Chinese medicine to enhance glucose homeostasis and protect pancreatic cells from high glucose-induced damage. However, the protection mechanism remains unclear.ObjectiveTo investigate the effect of SQC on INS-1 cell secretion and evaluate the associated mechanisms.MethodsINS-1 cells were cultured in serum augmented with or without NOD1 inhibitor ML130 (2μM) for 1 h, then exposed into a high glucose (50 mM) condition to simulate type 2 diabetes mellitus (T2DM) for 24 h and treated with different concentrations (0, 5, 10, 15, 20%) of SQC in serum for another 24 h. Then, the cell counting kit-8 (CCK-8) method, glucose-stimulated insulin secretion (GSIS) assay, transmission electron microscopy (TEM), real-time fluorescence quantitative reverse transcription polymerase chain reaction (RT-qPCR), and Western blot were performed for further investigation.ResultsUnder high glucose conditions, 15% SQC was the optimal therapeutic concentration, significantly improved INS-1 cell viability (p = 0.032) and enhanced insulin secretion (p < 0.0001). Ultrastructural analysis showed that after high glucose stimulation in GSIS, especially at 20 min, 15% SQC significantly increased both the total density (p = 0.143) and the mature ratio (p = 0.003) of insulin secretory vesicles. Furthermore, 15% SQC facilitated the dynamic transport of vesicles toward the cell membrane, evidenced by an increased vesicle density within 300 nm of the membrane at 10 min, followed by a subsequent decrease at 20 min—a trend consistent with that observed in the control group. Moreover, at the molecular level, 15% SQC intervention markedly up-regulated NOD1 and RIP2 protein expression (p = 0.029 and p < 0.0001) and transcription (p = 0.886 and p = 0.393) levels, while ML130 reversed the activation of the NOD1/RIP2 pathway.ConclusionsSQC promotes the maturation and transport of insulin secretory vesicles, thereby enhancing the secretory function of INS-1 cells in response to high glucose-induced damage. This protective effect may be associated with the activation of the NOD1/RIP2 signaling pathway.